Role of Interleukin- (IL-) 17 in the Pathogenesis and Targeted Therapies in Spondyloarthropathies - I-Tsu Chyuan; Ji-Yih Chen (Mediators of Inflammation)
Spondyloarthropathy (SpA) is a unique type of joint inflammation characterized by coexisting erosive bone damage and pathological new bone formation. Previous genetic association studies have demonstrated that several cytokine pathways play a critical role in the pathogenesis of ankylosing spondylitis (AS), psoriatic arthritis (PsA), and other types of SpA. In addition to several well-known proinflammatory cytokines, recent studies suggest that IL-17 plays a pivotal role in the pathogenesis of SpA. Further evidence from human and animal studies have defined that IL-17 and IL-17-producing cells contribute to tissue inflammation, autoimmunity, and host defense, leading to the following pathologic events associated with SpA. Recently, several clinical trials targeting IL-17 pathways demonstrated the positive response of IL-17 blockade in treating AS, indicating a great potential of IL-17-targeting therapy in SpA. In this review article, we have discussed the contributing role of IL-17 and different IL-17-producing cells in the pathogenesis of SpA and provided an outline of therapeutic application of the IL-17 blockade in the treatment of SpA. Other targeted cytokines associated with IL-17 axis in SpA will also be included.